PHYSIOTHERAPY MANAGEMENT IN PATIENT WITH URINARY INCONTINENCE: A CASE STUDY - Riani, Kurnia Ade; Supriyadi, Arin; Hayati, Ika (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Urinary incontinence (UI) is the problem of accidental or abnormal loss (leakage) of urine. The physiotherapy management of ES (Electrical Stimulation), Kegel Exercises, and Abdominal Muscle Exercise in increasing the strength of pelvic floor muscle and abdominal muscle strength in patients with urinary incontinence. Case Presentation: A female 25 year old comes to the doctor with complaints of difficulty urinating postpartum for 6 months, the doctor diagnoses the patient with urinary incontinence then referred to physiotherapy for further treatment Management and Outcome: Giving of electrical stimulation, kegel exercise, and abdominal muscle exercise effective to increase the strength of the pelvic floor muscle and abdominal muscle as well as decrease severity of urinary incontinence in patient urinary incontinence Discussion: After physiotherapy exercise interventions were given, the results obtained were an increase in the strength of the pelvic floor muscle from Pre-Test with a strength of the pelvic floor value of 2, an increase in strength of the pelvic floor to 3 at T8, an increase in the abdominal muscle strength at Pre-Test the result is 3 and becomes 4 at T8, and there is a decrease in severity of urinary incontinence at Pre-Test the result is 8 and becomes 6 at T8. Giving of electrical stimulation, kegel exercise, and abdominal muscle exercise effective to increase the strength of the pelvic floor muscle and abdominal muscle as well as decrease severity of urinary incontinence in patient urinary incontinence. Conclusion: After given by physiotherapy modalities and exercise in urinary incontinence it show a good progression. The physiotherapi’s treatment showed that there was an increase pelvic floor muscle strenght and abdominal muscle as well as decrease severity of urinary incontinence.